Influence of Mass Media in the Promotion of Community Development Programmes in Akinyele Local Government Area, Oyo State, Nigeria (American International Journal of Nursing Education and Practice, 2020)
The study examines the influence of mass media in the promotion of community development programmes in Akinyele Local Government Area, Oyo State, Nigeria. Descriptive research design of the survey type was used for this study. Four research questions were raised to guide the study. The population for this study consists of indigenes of Akinyele Local Government Area, Oyo State. Simple random sampling technique was used to select respondents from the study area. The respondents consist of one hundred and twenty respondents. The findings of the study reveals  that Mass media’s  main feature is disseminating information, they therefore use the opportunity in encouraging and mobilizing community members to community development programmets, It is revealed that practitioners organize programmes to educate community members and also uphold unity and progress in the community and it development programmes. This study therefore recommends that Mass media programme should organized by government occasionally to mobilize the adultson community development programmes, Community development programmes should be well supervised by the government and leaders in the society  and Adult practitioners should organize programmes to educate community members and also uphold unity and progress in the community and it development programmes. The study therefore concludes that community development could then be seen as a process of improving not just lives of the people of a locality and their ability to utilize resources available to them in improving their locality, but also the betterment of the interaction processes and forces that shape coexistence in the given locality.